ROENTGEN DIAGNOSTICS OF NECROTIZING ENTEROCOLITIS (NEC) IN NEWBORNS. - Shihov Y.O (Scholar Express Journals, 2023)
This is a non-specific inflammatory disease caused by infectious agents against the background of immaturity of local defense mechanisms and hypoxicischemic damage to the intestinal mucosa. Mortality ranges from 27 to 35%. Necrotizing enterocolitis (NEC) of newborns (Necrotizing enterocolitis, necrotizing enterocolitis, ulcerative necrotic enterocolitis, "disease of surviving prematurity) is a nonspecific inflammatory disease caused by infectious agents against the background of immaturity of local defense mechanisms and hypoxicischemic damage to the intestinal mucosa, prone to generalization of the process with development of a systemic inflammatory response
Keywords: GIT; Gastrointestinal tract; Premature newborn; Necrotizing Enterocolitis